Finnish Teachers' Attitudes About Muslim Students and Muslim Student Integration - Rissanen, Inkeri (Journal for the scientific study of religion, 2015)
Although there is much discussion of educational needs and how to integrate Muslim students into modern Western contexts, there is a shortage of research on teachers' attitudes about these issues. Finland offers a particularly interesting context for research, given its relatively new, small, yet rapidly growing Muslim population, its prominence of negative attitudes to visible religiosity, and its official policy of multiculturalism. This article presents the results of a quantitative study of Finnish teachers' attitudes to Muslim students and to their integration into Finnish schools. A nonprobability sample of Finnish preservice and practicing teachers (N = 864) was surveyed and the resulting data analyzed with exploratory factor analysis, t-tests, and ANOVA. The results indicate that Finnish teachers consider learning about general democratic values important, but their attitudes to dealing with Islam and Muslims are not quite as positive. However, previous involvement with other cultures indicated more positive attitudes among preservice teachers. Female teachers and practicing teachers were more oriented toward the teaching of commonality, and teaching at a more advanced level indicated more positive attitudes to Muslims and Muslim integration.